Suppressing GDF15 enhances the chemotherapeutic effect of 5 FU on MSI-H CRC by regulating the ferroptosis pathway SLC7A11/GSH/GPX4 - Zhi min Huang Fu; Ming Xiao; Hailun Xie; Shuxian Zhang; Tang Yi; Qingshu Li; Ming Li; Yalan Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Growth differentiation factor 15 (GDF15) is a member of the transforming growth factor beta (TGF-β) superfamily and is related to metabolism, injury, and aging. GDF15 has both tumor-promoting and tumor-suppressing effects. However, its role in colorectal cancer (CRC) with high microsatellite instability (MSI-H) must be further clarified. In our study, we found that GDF15 is generally elevated in pancarcinoma, particularly in colorectal cancer, and serves as an early indicator of the development of colorectal cancer. IHC and WB confirmed that GDF15 was elevated in MSI-H CRC clinical tissues and MSI-H CRC cell lines (HCT-116 and LoVo). Suppressing GDF15 by siRNA resulted in a substantial decrease in cell viability and proliferation. Furthermore, suppressing GDF15 can increase the sensitivity of MSI-H CRC cells to 5-fluorouracil (5-FU), which decreases cell viability and increases the apoptosis rate. In vivo experiments also demonstrated that mouse xenografts with suppressed GDF15 expression were more susceptible to 5-FU chemotherapy. We examined alterations in mitochondria via electron microscopy and changes in the mitochondrial membrane potential, ferroptosis-related signals (MDA, Fe2+), and SLC7A11/GSH/GPX4 protein pathway. Our research indicates that inhibiting GDF15 affects ferroptosis-related pathways, leading to ferroptosis and improving the MSI-H CRC response to 5-FU therapy. As a result, GDF15 could be a promising target for diagnosing and treating MSI-H CRC, potentially enhancing the overall effectiveness of therapy for patients with MSI-H CRC.